Comparison of Different Surgical Approaches for Hysterectomy: A Single-Institution Experience - Tohma, Yusuf Aytac; Tunc, Mehmet; Gunakan, Emre; Kucukyildiz, Irem; Atasoy Karakas, Latife; Moran, Utkun; Akyol, Mesut; Zeyneloglu, Hulusi Bulent; Dursun, Polat (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: We aimed to compare surgical outcomes and postoperative complications among different hysterectomy approaches such as total abdominal hysterectomy, vaginal hysterectomy, multiport access laparoscopic hysterectomy, and single-port access laparoscopic hysterectomy. Study Design: This retrospective, single institution, case control study was carried out at the Obstetrics and Gynecology Department of Baskent University in Ankara, Turkey. We evaluated 86 consecutive patients who underwent hysterectomy for benign gynecological conditions. Results: A total of 86 women underwent hysterectomy: 20 (23.3%) total abdominal hysterectomy, 20 (23.3%) vaginal hysterectomy, 27 (31.3%) multiport access laparoscopic hysterectomy, and 19 (22.1%) single-port access laparoscopic hysterectomy using a transumbilical single-port system. There was no significant difference in uterine size between groups (Z=5.705; p=0.127). A statistically significant (p<0.001) difference in operation time (duration of surgery) was observed among the following groups. The duration of surgery for the multiport access laparoscopic hysterectomy, and single-port access laparoscopic hysterectomy groups was similar, with these two laparoscopic procedures requiring significantly more time than total abdominal hysterectomy and vaginal hysterectomy procedures. There was no statistically significant difference in between hemoglobin levels before and after operation between groups. There was no statistically significant difference between groups in intraoperative and postoperative complications. Six patients experienced complications, one intraoperative and five postoperative. Intraoperative complication was ureter injury in single-port access laparoscopic hysterectomy group. The postoperative complication rate was 5.8% (5 cases) in 86 patients. Perirectal abscess in one patient and wound infection in two patients occurred in total abdominal hysterectomy group (15%). Urinary tract infection in one patient and vaginal cuff cellulitis in one patient occurred in vaginal hysterectomy group (4%). No complications were reported in multiport access laparoscopic hysterectomy, and single-port access laparoscopic hysterectomy groups. Post-surgery, all patients who underwent single-port access laparoscopic hysterectomy reported that they were satisfied with their incision and cosmetic results. Conclusions: When technically feasible, multiport access laparoscopic hysterectomy, and single-port access laparoscopic hysterectomy may be performed instead f total abdominal hysterectomy because of rapid recovery and shorter hospitalization however there are longer operating time.